Electrophysiology and Fluorescence Spectroscopy Approaches for Evaluating Gamete and Embryo Functionality in Animals and Humans - Raffaele Boni; Alessandra Gallo; Elisabetta Tosti (Biomolecules, 2022)
This review has examined two of the techniques most used by our research group for evaluating gamete and embryo functionality in animal species, ranging from marine invertebrates to humans. Electrophysiology has given access to fundamental information on some mechanisms underpinning the biology of reproduction. This technique demonstrates the involvement of ion channels in multiple physiological mechanisms, the achievement of homeostasis conditions, and the triggering of profound metabolic modifications, often functioning as amplification signals of cellular communication. Fluorescence spectrometry using fluorescent probes to mark specific cell structures allows detailed information to be obtained on the functional characteristics of the cell populations examined. The simple and rapid execution of this methodology allowed us to establish a panel helpful in elucidating functional features in living cells in a simultaneous and multi-parameter way in order to acquire overall drafting of gamete and embryo functionality.